Transition patterns of metabolism-weight phenotypes over time: A longitudinal study using the multistate Markov model in China - Zhang, Hongya; Tang, Xiao; Hu, Dongmei; Li, Guorong; Song, Guirong (Frontiers in Public Health, 2022)
Background: The change in weight or metabolic status is a dynamic process, but most studies only focused on metabolically healthy obesity (MHO) and the single transition between MHO and metabolically unhealthy obesity (MUO), thereby they did not fully reveal the nature of all possible transitions among metabolism-weight phenotypes over years. Methods: This was a longitudinal study based on a health check-ups retrospective cohort. 9742 apparently healthy individuals aged 20 to 60 at study entry were included and they underwent at least two health check-ups. Six metabolism-weight phenotypes were cross-defined by BMI categories and metabolic status, including metabolically healthy normal weight (MHNW), metabolically healthy overweight (MHOW), MHO, metabolically unhealthy normal weight (MUNW), metabolically unhealthy overweight (MUOW), and MUO. A multi-state Markov model was used to analyze all possible transitions among these phenotypes and assess the effects of demographic and blood indicators on the transitions. Results: The transition intensity from MUNW to MHNW was the highest (0.64), followed by MHO to MUO (0.56). The greatest sojourn time appeared in MHNW state (3.84 years), followed by MUO state (2.34 years), and the shortest appeared in MHO state (1.16 years). Transition intensities for metabolic improvement gradually decreased with BMI level, 0.64 for MUNW→MHNW, 0.44 for MUOW→MHNW, 0.27 for MUO→MHO , but those for metabolic deterioration, MHNW→MUNW, MHOW→MUOW, MHO→MUO, were 0.15, 0.38 and 0.56, respectively. Male, the middle-age group, the elevated alanine aminotransferase (ALT), aspartate aminotransferase (AST), and uric acid (UA) increased the risk of deterioration in weight or metabolic status and decreased the possibility of improvement in them. Conclusions: Maintaining a normal and stable BMI is important for metabolic health. More attention should be paid to males and the elder people to prevent their progression in metabolic and/or weight status. MHO is the most unstable phenotype and prone to convert to MUO state, and individuals with abnormal ALT, AST and UA are at increased risk of transiting to unhealthy weight or metabolic status, so we should be alert to the abnormal indicators and MHO. Intervention measures should be taken early to maintain healthy weight or metabolic status.